Human mesenchymal stromal cells inhibit platelet activation and aggregation involving CD73-converted adenosine - Netsch, Philipp; Elvers-Hornung, Susanne; Uhlig, Stefanie; Klüter, Harald; Huck, Volker; Janetzko, Karin; Wuchter, Patrick; Bugert, Peter; Bieback, Karen (Stem cell research & therapy, 2018)
Mesenchymal stromal cells (MSCs) are promising cell therapy candidates. Clinical application is considered safe. However, minor side effects have included thromboembolism and instant blood-mediated inflammatory reactions suggesting an effect of MSC infusion on hemostasis. Previous studies focusing on plasmatic coagulation as a secondary hemostasis step detected both procoagulatory and anticoagulatory activities of MSCs. We now focus on primary hemostasis and analyzed whether MSCs can promote or inhibit platelet activation.
Gesehen am 26.07.2018